Criminal Justice System Approach to Cyber Crime Criminalization In Legislation Science in Indonesia - Mhd. Ansor Lubis (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2021)
The development of information and communication technology causes world relations to become borderless and causes significant social, economic and cultural changes to take place rapidly. Computer-based information technology is currently a double-edged sword, because in addition to contributing to the improvement of human welfare, progress, and civilization, it is also an effective means of unlawful acts. On the one hand, technological advances have a positive impact, but also have a negative impact, with cyber crime. Viewed from the perspective of criminal law, efforts to overcome cyber crime with a penal policy and non-penal polic through a criminal court approach as a form of legal regulation to bring order to society by taking legal action determined by the House of Representatives together with the Government such as the special rules contained in Law Number 11 of 2008 concerning Information and Electronic Transactions and Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions and Regulation of the Criminal Code.